Inclusive development model: Women farmers and young farmers toward local food security - Mardhiah, Nellis; Pratama, Agus; Sari, Putri Kemala; Macella , Agatha Debby Reiza; Omalia, Noka; Saputra, Jumadil (UIN Ar-Raniry Banda Aceh, 2026)
This study aims to develop an inclusive agricultural development model to increase the participation of marginalized women farmers and young farmers in Nagan Raya Regency. This region is one of the nation’s food baskets, however the food security index has not been optimized with the targets set by the National Food Security Agency. Inclusive agricultural research relies on synergy between local governments and local communities which has not yet been integrated or specific. Therefore this study focuses on classifying groups of women farmers and young farmers who in an inclusive manner leverage local potential to achieve sustainable development goals. Data were analyzed using an inductive qualitative approach through data reduction verification and conclusion drawing. The results of this study show that an inclusive development model can be implemented through promoting female farmers’ participation and involving young farmers in transforming local resources in Nagan Raya Regency. The implementation of inclusive agriculture embraces the principle of empowering farmers’ resources within environmentally economically and socially oriented frameworks to enhance sustainable food security. Furthermore, the inclusive development model aims to achieve a green society a green economy and inclusive growth by strengthening the participation of women farmers and young farmers working together to support local food security. The implications of this research help classify the roles of various actors in achieving development priorities in agriculturally based regions of Nagan Raya and improving the regional food security index.